2006
DOI: 10.1007/s00403-006-0692-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of blood flow after topical application of benzyl nicotinate on different anatomic sites

Abstract: Cutaneous characteristics, e.g., thickness of the SC and density of follicles, affect the penetration of topically applied substances. In the present study, the penetration of benzyl nicotinate, causing a vasodilation, was studied on three anatomic sites (forearm, forehead and calf) differing in their skin characteristics. Therefore, the blood flow of the superficial dermal plexus and that of the larger capillaries in the deeper skin layers was simultaneously measured using a laser Doppler flowmeter. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…This hypothesis accords with previous work, which suggested that an enhanced blood flow allowed deeper tissue distribution of topically applied agents [53] , [54] , [55] . There could have been some synergy between the follicular transport enhancement and the increase in blood flow because the follicular structures are heavily vascularised, but this could not be confirmed with the current data set [56] , [57] . Organ uptake of the 14 C-labeled 10 kDa dextran following topical delivery ( Fig.…”
Section: Resultscontrasting
confidence: 57%
“…This hypothesis accords with previous work, which suggested that an enhanced blood flow allowed deeper tissue distribution of topically applied agents [53] , [54] , [55] . There could have been some synergy between the follicular transport enhancement and the increase in blood flow because the follicular structures are heavily vascularised, but this could not be confirmed with the current data set [56] , [57] . Organ uptake of the 14 C-labeled 10 kDa dextran following topical delivery ( Fig.…”
Section: Resultscontrasting
confidence: 57%
“…When the liniment is applied on the skin, the active ingredients, nicotinic acid esters (ethyl nicotinate, hexyl nicotinate), are converted to niacin (nicotinic acid) by cutaneous esterases after penetration into the skin. 35 At least two different physiological mechanisms account for the vascular component of the flushing, one involving activation of niacin receptors (GPR109A) in dermal Langerhans cells and keratinocytes, [36][37][38][39] leading to secretion of prostaglandins, the other activates the Capsaicin receptor (TRPV1) pathway. 40,41 In the end, both pathways produce vasodilation of arterioles and precapillary sphincters and subsequently increased capillary perfusion.…”
Section: Topical Application Of Linimentmentioning
confidence: 99%
“…28,[30][31][32]42,43 Hence, contactless cutaneous perfusion measurement at different depth is still the exclusive option due to the lack of appropriate instrumentation, and only few studies are available employing two-bandwidth LDI. For example, Jacobi et al 13,35 utilized a two-bandwidth laser Doppler (0.5 to 5 kHz and 5 to 30 kHz) instrument for measurement of cutaneous microcirculation at two different depths. 13,35 Much like our results, the authors reported higher perfusion in superficial capillaries compared to the deeper vasculature following liniment application.…”
Section: Topical Application Of Linimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacobi et al. [66] measured the responses of seven male human volunteers (23.1 ± 2.7 years) to benzyl nicotinate when applied to the forearm, forehead and calf. Using LDV, higher and faster basal blood flow values were observed for the forehead compared to the forearm and calf.…”
Section: Skin Response To Vasoactive Compoundsmentioning
confidence: 99%